2012
DOI: 10.4161/psb.19337
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs responsive to ozone-induced oxidative stress in Arabidopsis thaliana

Abstract: Ozone is a model abiotic elicitor of reactive oxygen species (ROS). ROS are important oxidative signaling molecules coordinating plant development and responses to biotic and abiotic stresses. Recently, microRNAs have been described as important players in regulating stress responses in plants. In this research we examined the miRNAs that are differentially expressed early in response to ozone in the Arabidopsis thaliana ecotype Col-0 that is tolerant to this oxidant. We used a plant miRNA array to identify 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…Four of the 23 selected genes were involved in oxidation–reduction processes ( AT1G77120 , AT3G11170 , AT4G31940 and AT4G27030 ), and it might be connected with accumulation of reactive oxygen species (ROS) that play a central role in coordinating defence signalling in plants in response to many abiotic stresses (Iyer et al ., ; Mittler, ). Cell membrane composition changes, such as changes in phospholipids and proteins, help to maintain membrane integrity, preserve cell compartmentalization and activate phospholipid signalling pathways in response to drought (Jarzyniak and Jasinski, ; Liu et al ., ; Ruelland et al ., ; Schulz, ).…”
Section: Discussionmentioning
confidence: 99%
“…Four of the 23 selected genes were involved in oxidation–reduction processes ( AT1G77120 , AT3G11170 , AT4G31940 and AT4G27030 ), and it might be connected with accumulation of reactive oxygen species (ROS) that play a central role in coordinating defence signalling in plants in response to many abiotic stresses (Iyer et al ., ; Mittler, ). Cell membrane composition changes, such as changes in phospholipids and proteins, help to maintain membrane integrity, preserve cell compartmentalization and activate phospholipid signalling pathways in response to drought (Jarzyniak and Jasinski, ; Liu et al ., ; Ruelland et al ., ; Schulz, ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated the response of miRNAs in Arabidopsis under ozone stress, which recorded altered response of 22 miRNAs [48]. Most of these miRNAs showed similar expression under UV-B stress, indicating the activation of similar regulating pathways under both types of stressors [48]. Such similarities in miRNA responses during ozone and UV-B stress could be expected, as both stresses lead to the production of reactive oxygen species (ROS) causing oxidative stress.…”
Section: Ozonementioning
confidence: 95%
“…Ozone enters the leaves through stomata, causes oxidative stress, decreases photosynthesis, damages DNA, protein, and cell membranes, and thereby negatively affects plant productivity [72À76]. A recent study investigated the response of miRNAs in Arabidopsis under ozone stress, which recorded altered response of 22 miRNAs [48]. Most of these miRNAs showed similar expression under UV-B stress, indicating the activation of similar regulating pathways under both types of stressors [48].…”
Section: Ozonementioning
confidence: 99%
See 1 more Smart Citation
“…Three miRNAs‐ (miR319, miR396 and miR408) mediated cold tolerance was also involved in the reduced levels of ROS during cold stress (Wang et al 2014a; Ma et al ; Zhang et al ). Moreover, Iyer et al () has identified 12 conserved miRNA families (including miR156, miR159, miR160 and miR166) that are differentially regulated by ozone (a model abiotic elicitor of ROS) in Arabidopsis (Iyer et al ). These conserved miRNAs were demonstrated to be involved in cold or heat stress response in many plant species (Table ).…”
Section: Mechanisms Of Temperature Stress Responses Of Small Rnasmentioning
confidence: 99%